PHILOSOPHICAL MEANINGS OF COLORS IN FINE ARTS - Ayubova Shohsanam Shukurjan's daughter; Akbarov R. M. (Web of Journals Publishing, 2024)
This article talks about the role, importance of colors in visual art, the symbolic and philosophical meanings of colors. In addition, observations of colors by famous artists are given.
Keywords: Leonardo da Vinci, the meaning of colors, the meaning of red, the meaning of white, yellow, green, blue, the meaning of colors in Sufism.